Effect of Herbagreen Nano-Particles on Biochemical and Technological Parameters of Cereals (Wheat and Corn) - Doloreza Prifti; Ardian Maçi (European Scientific Journal, ESJ, 2017)
This research study intended to provide evidence and proof of the positive effects, that applying of the Bio-Fertilizer Herbagreen produced through nanotechnology has on the agriculture in Albania. There are no doubts that nanotechnology is one of the most relevant innovations not only in agriculture, but also in other scientific fields such as biotechnology, medicine etc. Herbagreen nano-particles are able to directly penetrate plants after being applied, thus becoming immediately part of the plants lifecycle and metabolism. This is due to the new nano- and micro-dimensions of the grinded particles after being treated through TMAC (Tribo-Mechanical Activation of Calcite). This technology does not interfere with the mineral initial composition. It simply grinds the mineral particles in nano-dimensions and by so doing increases sensibly their contact surface. This makes these particles “magically” influence the yield quantity and quality in the treated plants. Based on the experiments performed during two consecutive years on the selected crops of corn and wheat, it was noticed that in addition to a yield increase in the plots treated with this nanotechnology, there was also an increase in the gluten values in wheat, while regarding the percentage values of proteins and lipids it was noted that the values of the treated plots with Herbagreen had the same values of the plots treated with the maximal dosage of chemical fertilizers. It was also concluded, that using of the Herbagreen fertilizers can avoid or reduce the soil and waters contamination caused by only traditional mineral fertilizers use. The financial costs for the treatment can be reduced as well.